Descubriendo a Valle-Inclán - Pascua Febles, Isabel (Servicio de Publicaciones y Difusión Científica de la ULPGC, 2013)
ppreciate the distorted grotesque and absurd reality. The third work comes to hand of Yolanda Arencibia, where relates to Valle-Inclán and Pérez Galdós. In a first approach, she intends to show the difference between Galdós and Valle-Incláns temperament: a shy, discreet and modest Galdós, facing an open-minded, somewhat exhibitionist, sneering personality and bohemian tendencies. Lastly, the essay from José Manual González collects the aestheticism and commitment: Bardem reads Valle-Inclán, who analyses from the cinematic perspective. González affirms Valle-Incláns interest in cinema and the connection of his prose and drama, especially Esperpento, with cinematic forms: "the writer believes in the cinema." However, adaptations of his works to the big screen has not been satisfactory as well as public acceptance or specialized reviews.